Pathogenesis and cell biology of amyotrophic lateral sclerosis (ALS) - Fratta, Pietro (Henry Stewart Talks, 2014)
Clinical features of ALS, ALS pathology and genetics, SOD1 related pathogenic mechanisms in ALS, RNA metabolism alterations in ALS, C9orf72 and ALS